How 'The Daily Mile™' works in practice: A process evaluation in a UK primary school. (9th October 2019) - Harris, Jennifer; Milnes, Linda Jane; Mountain, Gary
Over 75% children in the United Kingdom fail to achieve recommended levels of physical activity. Successful implementation of 'The Daily Mile™', a school-based physical activity intervention, could promote activity. We examined factors instrumental to replication and/or wider implementation of 'The Daily Mile' through application of a two phase multi-method process evaluation. Phase one: 75 children (mean age seven years eight months) from one East Midland primary academy trialled the intervention. Data collected were self-report logs, perceived exertion scores and structured observation. Phase two: a sub-sample of 18 stakeholders participated in focus groups which were analysed using framework method. Teachers delivered 'The Daily Mile' on 93.6% of school days. An average of 95.2% of students participated, 94.2% completed recommended 15 minutes, 94.3% to a moderate-to-vigorous level. Three themes emerged in focus groups; embedding 'The Daily Mile' into practice, creating the right physical environment and building relationships/promoting a supportive climate. With systematic organisation and planning, 'The Daily Mile' could emerge as an integrated means of increasing physical activity. A supportive climate and factors that promote resilience are key facilitators. Further research is needed to establish outcomes and cost-effectiveness.